Expressing accessory proteins in cellulolytic Yarrowia lipolytica to improve the conversion yield of recalcitrant cellulose - Zhong-peng Guo; Sophie Duquesne; Sophie Bozonnet; Jean-Marc Nicaud; Alain Marty; Michael Joseph O’Donohue (Biotechnology for Biofuels, 2017)
Abstract Background A recently constructed cellulolytic Yarrowia lipolytica is able to grow efficiently on an industrial organosolv cellulose pulp, but shows limited ability to degrade crystalline cellulose. In this work, we have further engineered this strain, adding accessory proteins xylanase II (XYNII), lytic polysaccharide monooxygenase (LPMO), and swollenin (SWO) from Trichoderma reesei in order to enhance the degradation of recalcitrant substrate. Results The production of EG I was enhanced using a promoter engineering strategy. This provided a new cellulolytic Y. lipolytica strain, which compared to the parent strain, exhibited higher hydrolytic activity on different cellulosic substrates. Furthermore, three accessory proteins, TrXYNII, TrLPMOA and TrSWO, were individually expressed in cellulolytic and non-cellulolytic Y. lipolytica. The amount of rhTrXYNII and rhTrLPMOA secreted by non-cellulolytic Y. lipolytica in YTD medium during batch cultivation in flasks was approximately 62 and 52 mg/L, respectively. The purified rhTrXYNII showed a specific activity of 532 U/mg-protein on beechwood xylan, while rhTrLPMOA exhibited a specific activity of 14.4 U/g-protein when using the Amplex Red/horseradish peroxidase assay. Characterization of rhTrLPMOA revealed that this protein displays broad specificity against β-(1,4)-linked glucans, but is inactive on xylan. Further studies showed that the presence of TrLPMOA synergistically enhanced enzymatic hydrolysis of cellulose by cellulases, while TrSWO1 boosted cellulose hydrolysis only when it was applied before the action of cellulases. The presence of rTrXYNII enhanced enzymatic hydrolysis of an industrial cellulose pulp and of wheat straw. Co-expressing TrXYNII and TrLPMOA in cellulolytic Y. lipolytica with enhanced EG I production procured a novel engineered Y. lipolytica strain that displayed enhanced ability to degrade both amorphous (CIMV-cellulose) and recalcitrant crystalline cellulose in complex biomass (wheat straw) by 16 and 90%, respectively. Conclusions This study has provided a potent cellulose-degrading Y. lipolytica strain that co-expresses a core set of cellulolytic enzymes and some accessory proteins. Results reveal that the tuning of cellulase production and the production of accessory proteins leads to optimized performance. Accordingly, the beneficial effect of accessory proteins for cellulase-mediated degradation of cellulose is underlined, especially when crystalline cellulose and complex biomass are used as substrates. Findings specifically underline the benefits and specific properties of swollenin. Although in our study swollenin clearly promoted cellulase action, its use requires process redesign to accommodate its specific mode of action.